PENGARUH PENYAJIAN LAPORAN KEUANGAN DAN SISTEM PENGENDALIAN INTERN TERHADAP AKUNTABILITAS PENGELOLAAN KEUANGAN DAERAH (Studi Empiris Pada Organisasi Perangkat Daerah Pemerintah Kota Ambon) - Silooy, Revy Wilhelmina (Jurusan Akuntansi Fakultas Ekonomi dan Bisnis, 2023)
The purpose of this study was to examine the effect of the presentation of financial statements and the internal control system on the accountability of regional financial management. The object of research is 35 Regional Apparatus Organizations (OPD) of the Ambon City Government. Meanwhile, the samples were the head of OPD, the head of the accounting/finance sub-section, the revenue treasurer, and the expenditure treasurer as well as the government's internal auditor. Purposive sampling is a sampling technique used in this study. The criteria used in this sampling technique are: 1. Head of OPD, head of accounting/finance sub-section, revenue treasurer, expenditure treasurer and government internal auditor who has a minimum education of S1 at the Ambon City Government. 2. Head of OPD, head of sub-section of accounting/finance, treasurer of revenue, treasurer of expenditure and government internal auditor who has experience in holding his position for at least 1 year in Ambon City Government. The analytical tool used is multiple linear regression. The results of the study prove that the presentation of financial statements has a significant effect on the accountability of regional financial management. The internal control system has a significant effect on the accountability of regional financial management.